ANALISIS PERUBAHAN PENGGUNAAN AIR BERSIH SEBELUM DAN SESUDAH TERJADI KENAIKAN TARIF PDAM DI KABUPATEN BANGLI - Yekti, Mawiti Infantri; Kerta Arsana, I Gusti Ngurah; Aryasavira, Made Dwita Berlian (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2020)
In 2013 the Bangli Regency Government and the Bangli Regency PDAM agreed to make a new policy related to the increasing of clean water tariffs in the Bangli and Tembuku Districts. This study aims to bring up the trend of changes before and after the PDAM tariff increase of 118%, so that it can be used as a basis for further Bangli PDAM decision making. This study uses a simple random sampling method by randomly taking the samples studied without looking at the strata, and samples are scattered as many as 80 samples in Bangli District and as many as 75 samples in Tembuku District. The analysis showed that the use of clean water experienced a declining trend after the tariff increase of 25.28% based on the survey and 25.31% based on the provision of the PDAM in the Bangli District. Whereas in Tembuku District the reverse trend showed an increase after the tariff increase of 14.08% based on the survey and 14.07% based on the provision of the PDAM. Changes in the use of clean water on average per person / day is influenced by water needs based on the number of family members in each house per month.